The 10 principles of open business : building success in today's open economy - Cushman, David; Burke, Jamie (Basingstoke, Hampshire Palgrave Macmillan, an imprint of Macmillan Publishers Limited, 2014)
The revolutionary power of the internet has accelerated the demand for a totally new kind of business. Stakeholders now demand more open, connected and meaningful relationships with organizations, and the world's leading brands are taking note. But whilst many have the ambition to become'open businesses', few have the ability to get there.'The 10 principles of open business' is a serious, challenging, wide-ranging and practical guide to organizational design for the twenty-first century.
Keywords: Organizational change; Organizational effectiveness